If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 260 + -3x = 42x + 15 Reorder the terms: 260 + -3x = 15 + 42x Solving 260 + -3x = 15 + 42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42x' to each side of the equation. 260 + -3x + -42x = 15 + 42x + -42x Combine like terms: -3x + -42x = -45x 260 + -45x = 15 + 42x + -42x Combine like terms: 42x + -42x = 0 260 + -45x = 15 + 0 260 + -45x = 15 Add '-260' to each side of the equation. 260 + -260 + -45x = 15 + -260 Combine like terms: 260 + -260 = 0 0 + -45x = 15 + -260 -45x = 15 + -260 Combine like terms: 15 + -260 = -245 -45x = -245 Divide each side by '-45'. x = 5.444444444 Simplifying x = 5.444444444
| -7a^2= | | 49+20(2)= | | -2a+2=1 | | 6-8x=15-36x | | 6-8x=15-6x | | x^2-11x+25=3x+1 | | 6=5x-5 | | 3-y=-31 | | 7-2x=x | | x^2-4x-17=4 | | -4d=5d-17 | | 2x+15-x=14 | | 17a+17b= | | 130.74=179.4*n | | 3X+6=43+X | | 130.6=283.2*n | | 15-6t=-11t | | -11/4x=7 | | 2x+5=7x-4 | | 3w^2+8w+5= | | 13*x^2-8=5 | | (3+5x)(3-5x)= | | 9+3n=(4+5)3-6 | | y=ln(x^2-9) | | 12+8m=100 | | 13*x^2-11=3 | | h/6-29=-21 | | y=(x-5)/(x+5) | | (25+35x)/15=4 | | (3x^2)-(44x)+120=0 | | 8-s=4t+3 | | f(x)=x^2-9 |